2012
DOI: 10.2139/ssrn.2051379
|View full text |Cite
|
Sign up to set email alerts
|

Why Do UK Banks Securitize?

Abstract: The eight years from 2000 to 2008 saw a rapid growth in the use of securitization by UK banks. We aim to identify the reasons that contributed to this rapid growth. The time period (2000 to 2010) covered by our study is noteworthy as it covers the pre-…nancial crisis creditboom, the peak of the …nancial crisis and its aftermath. In the wake of the …nancial crisis, many governments, regulators and political commentators have pointed an accusing …nger at the securitization market -even in the absence of a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In a US based study, (Uzun and Webb, 2007) find that bank size is an important determinant of whether a bank will securitize. (Cerrato et. al, 2012) utilize a sample of UK banks and find that the need to securitize tends to be driven by the search for liquidity, followed by regulatory arbitrage and credit risk transfer.…”
Section: Benefits and Costs Of Securitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a US based study, (Uzun and Webb, 2007) find that bank size is an important determinant of whether a bank will securitize. (Cerrato et. al, 2012) utilize a sample of UK banks and find that the need to securitize tends to be driven by the search for liquidity, followed by regulatory arbitrage and credit risk transfer.…”
Section: Benefits and Costs Of Securitizationmentioning
confidence: 99%
“…However, there are potential drawbacks associated with the securitization process (Schwarcz, 1991(Schwarcz, , 2009Cerrato et al, 2012). It is the credit ratings process that has come in for much criticism in the aftermath of the financial crisis (Scalet and Kelly, 2012).…”
Section: Benefits and Costs Of Securitizationmentioning
confidence: 99%
“…Even if it is difficult to disentangle empirically the relative importance of each of the two motives, there is some relevant evidence in favor of financial innovation as a key factor behind shadow banking. For example, support for the notion of securitization as a tool to increase the efficiency of risk sharing and liquidity transformation, rather than regulatory arbitrage, can be found in Minton, Sanders, and Strahan (2004) for the United States, Bannier and Hansel (2008) for Europe, and Cerrato et al (2012) for the United Kingdom. Another common finding of these papers, related to one of the main results of this model, is that banks more involved in securitization tend to originate lower quality loans.…”
Section: Discussionmentioning
confidence: 99%
“…37 Research carried out in UK banks has shown that a positive link exists between securitisation and bank credit risk where securitisation has been significantly driven by: i) the search for liquidity funding and ii) regulatory capital arbitrage and credit risk transfer. 38 It is to regulators' credit to attempt and modify/influence bank behaviour towards the 'appropriate' direction through steering banks to re-think and de-leverage their business models. That is, banks will have to amend their business models considerably before they are in a position to originate assets that are fully viable and designated for use as safe collateral.…”
Section: Liquidity Credit Constriction and Capital Arbitragementioning
confidence: 99%